Exploration Of Brand Love And E-Trust In Forming Revisit Intention In Generation Z: A Qualitative Study On Shopping Experience On Live Tiktok - Mala, Iva Khoiril; Anam, Choirul; Pratikto, Heri; Saptaria, Lina (Fakultas Ekonomi Universitas Kadiri, 2025)
This study aims to explore how brand love and e-trust are formed among Generation Z in the context of purchasing products through live TikTok, as well as how these two factors contribute to users' intentions to reuse the platform. The method employed is a qualitative approach using in-depth interview techniques with 10 informants who are active users of Live TikTok, allowing for the exploration of their subjective and emotional experiences. The results show that direct interaction with creators and content on Live TikTok creates a strong emotional connection (brand love) and increases user trust in the platform (e-trust). These two factors proved significant in motivating users' intention to return to using TikTok's Live feature as an alternative to online shopping. This research confirms that building emotional relationships and trust with users is critical for brands in today's digital marketing context.